Sanctus - definicje wobec tekstowego znaczenia słowa w pismach św. Izydora z Sewilli - Ledzińska, Anna (Vox Patrum, 2022)
St. Isidore of Seville, who lived at the turn of the 6th and 7th century in Visigothic Spain, on the one hand collected in his works the heritage of the ancient world, and on the other became one of the most important auctoritates of the Middle Ages. He lived at the time of historical, cultural and political upheaval, and change in the surrounding world usually generates linguistic change. The article tends to check how the views on sanctity expressed explicitly by Isidore, using lexeme ’sanctus’, relate to those immanent in his language. Therefore, three definitions of ’sanctus’ contained in Etymologies and the work On the Differences between Words were analyzed from the viewpoint of semantics and sources. Nextly, they were compared with textual occurrences of the word in the corpus of all works by Isidore of confirmed authenticity. The latter were studied using corpus-based methods, with the SketchEngine software. Additionally, lexicographical material contained in several dictionaries of classical and ecclesiastical Latin was used as a background for the analysis. The results indicate the ancient provenance of the meanings of the lexeme ’sanctus’ declared in the definitions and a different, clearly medieval, ecclesiastical semantic profile of the word in the corpus of Isidorian texts. The study reveals the process of adaptation of the Latin language to changing circumstances, the transformation of concepts and the world of thought under the influence of Christianity at the threshold of the Middle Ages in the works of one of the most important authors of that period.